Effects of heteroatom substitution in spiro-bifluorene hole transport materials. Issue 8 (25th May 2016) - Hu, Zhao; Fu, Weifei; Yan, Lijia; Miao, Jingsheng; Yu, Hongtao; He, Yaowu; Goto, Osamu; Meng, Hong; Chen, Hongzheng; Huang, Wei
Abstract : By introducing the heteroatom into the benchmark hole transport material Spiro-MeOTAD, the energy level of hole transport materials can be tuned. Abstract : Three new spirofluorene-based hole transport materials, Spiro-S, Spiro-N, and Spiro-E, are synthesized by replacing the para -methoxy substituent in 2, 2′, 7, 7′-tetrakis( N, N -di- p -methoxyphenylamine)-9, 9′-spirobifluorene (Spiro-MeOTAD) with methylsulfanyl, N, N -dimethylamino and ethyl groups. Their properties as hole transport materials in perovskite solar cells are investigated. The impact of replacing the para -methoxy substituent on bulk properties, such as the photophysical properties, HOMO/LUMO energy level, hole extraction properties and morphologies of perovskite thin films are investigated. Their optoelectronic and charge-transport properties and performance in perovskite solar cells are compared with the current benchmarked and structurally-related hole transport material (HTM) Spiro-MeOTAD. Surprisingly, the methylsulfanyl substituted spirofluorene shows the highest power conversion efficiency of 15.92% among the investigated spirofluorenes, which is an over 38% increase in PCE compared with that of Spiro-MeOTAD under similar device fabrication conditions.